Drugs that Mimic the Effect of Gene Mutations for the Prevention or the Treatment of Atherosclerotic Disease: From PCSK9 Inhibition to ANGPTL3 Inactivation - Athyros, Vasilios G.; Katsiki, Niki; Dimakopoulou, Aikaterini; Patoulias, Dimitrios; Alataki, Sofia; Doumas, Michael (Current Pharmaceutical Design, 2018)
Background: Drugs mimicking natural beneficial mutations, including that for familial hypercholesterolemia (FH), might represent the future of hypolipidemic drug treatment. Objective: The aim of this review is to review the properties and the effects of these drugs, which are either already commercially available or are in the process to be approved for the treatment of dyslipidemia. Results: More than a decade ago, it was accidentally discovered that proprotein convertase subtilisin/kexin type 9 (PCSK9) loss-of-function mutations resulted in marked lifelong reduction of LDL-C and the incidence of cardiovascular disease (CVD). This provided the idea for a human anti-PCSK9 antibody. Along with dozens of phase II and III studies demonstrating unprecedented reductions in LDL-C levels, two large clinical trials established the substantial benefits of evolocumab and alirocumab on cardiovascular morbidity and mortality, on top of standard treatment. Evolocumab and alirocumab are now approved and used in clinical practice for the treatment of FH, statin intolerance, and high risk patients not achieving LDL-C targets. Anti RNA, small molecules, peptides and also protein fragments against PCSK9 are in phase 1 trials. Angiopoietin-like protein 3 (ANGPTL3) regulates lipid metabolism increasing triglycerides (TGs), remnants, and LDL-C. In a huge study, ANGPTL3 deficiency due to gene(s) loss-of-function was associated with substantial reductions in circulating TGs, LDL-C, and CVD. Evinacumab, an ANGPTL3 antibody, caused a dose-dependent reduction in fasting TG levels of up to 76% and LDL-C of up to 23% and CVD risk by 41%. There is also antisense oligonucleotide and micro-RNA- 27b (miR-27b) against ANGPTL3. Two naturally occurring mutations in apo3 gene, A23T and K58E, reduce TGs and CVD risk. A monoclonal antibody targeting apoC-III has the same effect. Conclusion: Mimicking the beneficial naturally happening mutations in lipid metabolism pathways with biological drugs is probably the future of hypolipidemic drug treatment.
Keywords: Familial Hypercholesterolemia